Information Security Practices Emerging Threats and Perspectives - Traoré, Issa.; Awad, Ahmed; Woungang, Isaac; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This book introduces novel research targeting technical aspects of protecting information security and establishing trust in the digital space. New paradigms, and emerging threats and solutions are presented in topics such as application security and threat management; modern authentication paradigms; digital fraud detection; social engineering and insider threats; cyber threat intelligence; intrusion detection; behavioral biometrics recognition; hardware security analysis. The book presents both the important core and the specialized issues in the areas of protection, assurance, and trust in information security practice. It is intended to be a valuable resource and reference for researchers, instructors, students, scientists, engineers, managers, and industry practitioners. .
Chapter 1.Introduction - Emerging Threats call for New Security Paradigms -- Chapter 2. Botnets Threat Analysis and Detection -- Chapter 3. Collective Framework for Fraud Detection using Behavioral Biometrics -- Chapter 4. The Hardware Trojan System: An On-line Suite of Tools for Hardware Trojan Analysis -- Chapter 5. The Hardware Trojan System: An On-line Suite of Tools for Hardware Trojan Analysis -- Chapter 6. Ensuring Online Exam Integrity through Continuous Biometric Authentication -- Chapter 7.An Enhanced CUSUM Algorithm for Anomaly Detection -- Chapter 8. Conclusion: Future Trends and Challenges.
Keywords: Telecommunication; Computer networks .; Data protection; Security systems; Biometric identification; Communications Engineering, Networks; Computer Communication Networks; Data and Information Security; Security Science and Technology; Biometrics